LIGHT/TNFSF14 Levels in Carotid Plaques Are Associated With Symptomatic Cerebrovascular Disease - Gonçalves, Isabel ; 0000-0002-2935-0181; Sun, Jiangming ; 0000-0001-6814-1297; Singh, Pratibha; Pan, Mengyu ; 0000-0002-9899-1345; Gialeli, Chrysostomi; Bengtsson, Eva ; 0000-0001-7075-1772; Nilsson, Jan; Lutgens, Esther; Edsfeldt, Andreas ; 0000-0002-2691-9192; Shami, Annelie ; 0000-0002-6976-4397 (Journal of Stroke, 2025)
Background and Purpose Plaque rupture is the underlying cause of most cardiovascular events, such as stroke and myocardial infarction. The co-stimulatory molecule LIGHT (tumor necrosis factor superfamily member 14, TNFSF14) has been detected in foam cell-rich regions of atherosclerotic plaques, but whether it has a role in plaque stability is not known. This study investigates the association between intraplaque LIGHT levels and plaque vulnerability. Methods LIGHT levels were measured in homogenates of carotid endarterectomy samples by proximity extension assay (n=202) and through bulk RNA sequencing and spatial transcriptomics (Visium) of plaques from patients included in the Carotid Plaque Imaging Project. Homogenates were further examined by multiplex analyses and enzyme-linked immunosorbent assay, and plaque sections by immunohistochemistry. Results Plaque levels of LIGHT were associated with occurrence of preoperative cerebrovascular symptoms, including stroke. LIGHT levels correlated with a histological plaque vulnerability index, necrotic core size, and inflammatory cytokine levels. Additionally, expression of extracellular matrix turnover machinery components, including the collagen cross-linking proteoglycan fibromodulin and matrix metalloproteinases 1, 2, 9, and 10, was associated with plaque LIGHT levels. Conclusion Expression of LIGHT in atherosclerotic plaques not only correlates with markers of plaque destabilization, but is also significantly elevated in plaques from symptomatic compared to those from asymptomatic patients. These results associate LIGHT content with a rupture-prone plaque phenotype, potentially upregulated as part of a reparative response, warranting further studies.
Publisher Copyright: © 2025 Korean Stroke Society.
Keywords: Atherosclerosis; Carotid arteries; Plaque; TNFSF14